Exercise mode and attentional networks in older adults: a cross-sectional study - Biye Wang; Wei Guo (PeerJ, 2020)
Background Previous studies have indicated that physical exercise enhances attentional function; however, the relationship between exercise mode and attentional networks has not been clarified for older adults (>60 years old). This study aimed to investigate the relationship between attentional networks and different exercise modes in older adults. Methods Two hundred and fifty-nine participants aged between 60 to 81 years were enrolled and classified into three groups (closed-skill group, open-skill group, or sedentary control group) using an exercise-related questionnaire. All participants completed an attention network test (ANT), which measured executive control, orienting, and alerting networks. Results The open-skill group had significantly higher executive network efficiency compared to the closed-skill (p < 0.01) and sedentary (p < 0.01) groups. The closed-skill group had significantly higher values compared to the sedentary control group (p < 0.05). Differences were not detected among groups for alerting and orienting networks (p > 0.05). The open-skill group had significantly higher values compared to the sedentary control group regarding proportion score of executive network (p < 0.01). In comparison, no significant differences were detected among groups for proportion scores of alerting and orienting networks. Conclusion This study extends current knowledge by demonstrating that open-skill exercises selectively enhance the executive control of attentional networks in older adults. Open-skill exercises combines physical exercise and cognitive training, potentially representing a more effective exercise mode to maintain or enhance attentional function in older adults.